Perbandingan Metode Certainty Factor dan Dempster-Shafer Pada Sistem Pakar Diagnosa Penyakit Gigi dan Mulut - Muhammad Husni Rifqo; Dedy Agung Prabowo; Muflih Haura (Universitas PGRI Semarang, 2019)
Health is one of the essential human requirements in addition to food, housing and education, because only in a healthy state humans can live, grow and work better. Numerous people who are less concerned about health, especially on oral and dental health because of dental and oral diseases can strike anyone and anytime. Certainty factor is a method to prove whether a fact is certain or uncertain in the form of metrics that are usually used in expert systems. This method is just righ for expert systems that diagnose something uncertain. Dempster-Shafer is a mathematical theory for evidence based on belief functions and plausible reasoning, used to mingle separate pieces of information (evidence) to estimate the probability of an event. Thus, appear a problem on how to make expert system with two comparison of certainty factor and dempster-shafer methods on the expert system diagnosing dental and dental diseases. The objective of the research was to contribute a solution by building an application that can determine the dental and mouth disease fast and efficient. It is hoped that this application can be developed into another cases so that it extend the insight of smarthphone based java program.